White sponge nevus: A Case report and clinical update on the diagnosis - Ranjana Garg; Vivek V Gupta; Anand S Tegginamani; Vanishree H Shivakumar (Wolters Kluwer Medknow Publications, 2022)
Hereditary white lesions are a rare occurrence in the oral cavity. These lesions are usually harmless and benign. But these lesions resemble the other pathological oral white lesions having the risk of malignant transformation. The diagnosticians should be aware of the existence of these benign white lesions to avoid misdiagnosis and timely intervention for potentially malignant disorders. We have reported the occurrence of white sponge nevus in a young male patient and his mother. The patient's family history, complete clinical examination, and histological report validated the clinical diagnosis.